Upaya Guru Tahfidz dalam Meningkatkan Hafalan al-Qur'an Siswa di Pondok Pesantren Putri Al-Muslimun Magetan: Optimization the Efforts of Tahfidz Teachers in Improving Qur’an Memorization of Students at Al-Muslimun Islamic Boarding School for Girls, Magetan - Aisyah Istikomah; Nurul Aiman; Azid Syukroni (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2025)
Islamic boarding schools remain a primary reference in Islamic education, as they are deeply rooted in cultural traditions and supported by a growing public awareness of the importance of religious learning. The increasing demand for Qur’anic memorization, especially in today’s dynamic and challenging social environment, has encouraged many Muslim parents to entrust their children’s education to formal institutions offering structured and intensive tahfidz al-Qur’an programs. These programs aim not only to produce students who can accurately memorize the Qur’an but also to nurture individuals who uphold Islamic values and possess commendable character. Al-Muslimun Islamic Boarding School for Girls in Magetan is one such institution, offering a pesantren-based tahfidz program targeting the memorization of all 30 juz of the Qur’an bil ghaib. This study aims to explore the optimization of tahfidz teachers’ efforts in enhancing students’ Qur’anic memorization, analyze the learning outcomes, and identify the key challenges encountered in the process. This research adopts a descriptive qualitative approach, with data collected through interviews, participatory observation, and document analysis. Data analysis was conducted through data reduction, presentation, and conclusion drawing, validated by source triangulation. The findings reveal that: (1) Teachers’ efforts include strengthening memorization targets, tasmi’ al-Qur’an, stage-based testing, as well as appreciation and rewards. (2) The results show achievement of memorization targets, fluency, and memorization quality. (3) Challenges include school branding, public trust, and national event participation.